Toxicity Assessment and Control of Early Blight and Stem Rot of Solanum tuberosum L. by Mancozeb-Loaded Chitosan-Gum Acacia Nanocomposites - Ravinder Kumar; Joginder Singh Duhan; Anju Manuja; Pawan Kaur; Balvinder Kumar; Pardeep Kumar Sadh (MDPI AG, 2022)
Biopolymers such as chitosan and gum acacia are used for nanotechnological applications due to their biosafety and ecofriendly nature. The commercial fungicide mancozeb (M) was loaded into chitosan-gum acacia (CSGA) polymers to form nanocomposite (NC) CSGA-M (mancozeb-loaded) measuring 363.6 nm via the ionic gelation and polyelectrolyte complexation method. The physico-chemical study of nano CSGA-M was accomplished using dynamic light scattering (DLS), scanning electron microscope (SEM), transmission electron microscope (TEM), X-ray diffraction (XRD), and thermogravimetric analysis (TGA). Nano CSGA-M-1.0 (containing 1.0 mg/mL mancozeb) at 1.5 ppm demonstrated a maximum inhibition (83.8 ± 0.7%) against Alternaria solani, while Sclerotinia sclerotiorum exhibited a 100% inhibition at 1.0 and 1.5 ppm through the mycelium inhibition method. Commercial mancozeb showed an inhibition of 84.6 ± 0% and 100%, respectively, for both fungi. In pot house conditions, NCs were found to exhibit good antimicrobial activity. Disease control efficiency (DCE, in %) in pathogen-treated plants for CSGA-M-1.0 was 64.6 ± 5.0 and 60.2 ± 1.4% against early blight and stem rot diseases, respectively. NCs showed lower cytotoxicity than commercial mancozeb at the given concentration. In conclusion, both in vitro and in vivo antifungal efficacy for nano CSGA-M was found to be quite comparable but less toxic than mancozeb to Vero cell lines; thus, in the future, this formulation may be used for sustainable agriculture.